New records of Caligidae (Copepoda, Siphonostomatoida) from the Philippines - Maran, Balu Alagar Venmathi; Cruz-Lacierda, Erlinda R.; Ohtsuka, Susumu; Nagasawa, Kazuya (Zootaxa, 2016)
Parasitic copepods, especially sea lice (Caligidae) are causing economic problems in both aquaculture and to wild fishes around the world, but their study in at least some of the southeastern Asian countries, is still scanty. Here we provide new information on the distribution of 11 known species of parasitic copepods collected from 11 marine fish hosts from Iloilo, central part of the Philippines. Two species of the genus Anuretes Heller, 1865 and nine species of the genus Caligus Müller, 1785 were found to infest these hosts, i.e. Anuretes branchialis Rangnekar, 1953 from Platax orbicularis (Forsskål, 1775); A. plectorhynchi Yamaguti, 1936 from P. orbicularis and Plectorhinchus pictus (Tortonese, 1936); Caligus absens Ho, Lin et Chen, 2000 from Priacanthus macracanthus Cuvier in Cuvier & Valenciennes, 1829; C. asymmetricus Kabata, 1965 and C. coryphaenae (Steenstrup & Lütken, 1861) from Auxis thazard (Lacepède, 1800); C. bonito Wilson, 1905 from Coryphaena hippurus Linnaeus, 1758; C. cordyla Pillai, 1963 from Megalaspis cordyla (Linnaeus, 1758); C. cornutus Heegaard, 1962 from Sphyraena jello Cuvier in Cuvier & Valenciennes, 1829; C. epinepheli Yamaguti, 1936 from Scomberoides commersonnianus Lacepède, 1801; C. kanagurta Pillai, 1961 from Decapterus kurroides Bleeker, 1855, D. macarellus (Cuvier in Cuvier & Valenciennes, 1833) and C. hippurus; and C. rotundigenitalis Yü, 1933 from Scatophagus argus (Linnaeus, 1766). Attachment sites included the gill filaments and the body surface. Prevalence and mean intensity of caligids are provided in addition to an update on the checklist of caligids of the Philippines. Although reports on caligids in the Philippines are few, the published records indicate that sea lice are widely distributed throughout the archipelago.